391 NEUROLOGICAL DISORDERS AND TAKOTSUBO SYNDROME: CLINICAL FEATURES AND OUTCOMES. RESULTS FROM A MULTICENTER PROSPECTIVE EUROPEAN REGISTRY OF 2300 PATIENTS. (15th December 2022) - Vitale, Enrica; Santoro, Francesco; Cetera, Rosa; Ragnatela, Ilaria; Mallardi, Adriana; Leopizzi, Alessandra; Matera, Annalisa; Correale, Michele; Iacoviello, Massimo; Brunetti, Natale Daniele
Abstract: Background and aims: Takotsubo syndrome (TTS) is an acute heart failure syndrome featured by a reversible left ventricular systolic dysfunction. However, few data have been reported about prevalence of non-cardiovascular comorbidities as chronic neurological disorders in TTS patients. Aim of this study was to compare clinical features, short- and long-term outcome among TTS patients with history of neurological disorder. Methods: 2301 patients with TTS were enrolled in a multicenter prospective European registry from July 2002 to November 2021. Clinical features, in- and out-of-hospital MACE, laboratory and imaging data were collected and a long-term follow-up was performed. Results: Prevalence of history of neurological disorder was 17% (n= 400 pts). Most represented neurological conditions were previous cerebrovascular disorders (ischemic stroke and transient ischemic attack, 36.2%), followed by neurodegenerative disorders (30.7%, including cognitive disorders and motion disorders), tensive migraine (10%) and epilepsy (9.5%). Neurological Patients developed TTS more frequently after a physical trigger (46.2% vs 33.8%, p<0.01). Sepsis (10%), acute neurological trigger (9.5%) and extreme activity/trauma (8.5%) where the type of physical trigger more prevalent. During hospitalization neurological patients had longer in-hospital stay (10±11 days vs 8±8 days, p<0.01) and experienced more often in-hospital complications (27% vs 16%, p=0.0001) mainly driven by cardiogenic shock and in-hospital death (12% vs 7.6%; 6.5% vs 2.8%, respectively p<0.01). Long-term mortality was higher in patients with history of neurological disorders (23.5% vs 10%, p<0.01), with a mean follow up of 2.5 ± 5.8 years. Conclusions: Patients with history of neurological disorders and TTS have different clinical features and worse prognosis with higher short-term and long-term mortality.